THE EMERGING ECONOMIES CLASSIFICATION IN TERMS OF THEIR DEFINING, GROUPING CRITERIA AND ACRONYMS USED FOR THIS PURPOSE - Daniela-Neonila, Mardiros; Roxana-Manuela, DICU (Strategii Manageriale)
The starting point of this paper is represented by an evolutionary approach of the terminology used to define the term of emerging economy, of the review of the acronyms used for the purpose to group some of these economies in relation to certain criteria. The approach of the emerging economies is followed by the presentation and the systematization of some of the definitions that, during the time, was given by certain personalities, groups and international organizations to this concept. Talking about economies, some of the important indicators in the award of the emerging economy status are those who take into consideration the income and the economic growth rate illustrated in this paper by GDP. Subsequently of the screening realized for the mentioned characteristics set was taken into consideration the mode how they are manifested in a number of emerging economies of Europe.